Nonrenewable Energy Cost and Greenhouse Gas Emissions of a "Pig-Biogas-Fish" System in China. (8th November 2012) - Yang, Qing; Wu, Xiaofang; Yang, Haiping; Zhang, Shihong; Chen, Hanping
Abstract : The purpose of this study is to assess the energy savings and emission reductions of the present rural biogas system in China. The life cycle assessment (LCA) method is used to analyze a "pig-biogas-fish" system in Jingzhou, Hubei Province, China. The nonrenewable energy cost and the greenhouse gas (GHG) emissions of the system, including the pigsty, the biogas digester, and the fishpond, are taken into account. The border definition is standardized because of the utilization of the database in this paper. The results indicate that the nonrenewable energy consumption intensity of the "pig-biogas-fish" system is 0.60 MJ/MJ and the equivalent CO2 emission intensity is 0.05 kg CO2 -eq/MJ. Compared with the conventional animal husbandry system, the "pig-biogas-fish" system shows high renewability and GHG reduction benefit, which indicates that the system is a scientific and environmentally friendly chain combining energy and ecology.